DATA SECURITY OF MEDICAL CHECKUP INFORMATION SYSTEM IN MILITARY HOSPITAL - Setyaningrum, Leli; Syahlan, Zainal; Isnadi, Isnadi (Faculty of Science and Technology University of Pramita Indonesia, 2025)
The medical checkup (MCU) information system is essential for maintaining activities in hospitals and health facilities. Development of a system that prioritizes the security of patient data and information contained therein. In military hospitals, patient condition data is soldier condition data that must be guaranteed security against various forms of data and information leaks. Thus, an appropriate security method is needed that can support the prevention of various forms of cybercrime attacks and data leaks. The military has more than one hospital that was established to support various military operations, so the system used is also an integrated system that can reach all existing hospitals and health facilities.